Los trabajos de las mujeres y la economía de las unidades domésticas en la Grecia Clásica - Mirón Pérez, Mª Dolores (Complutum, 2007)
In this article women’s work inside the domestic unit of Classical Greece is analyzed. Most of economic activities were carried out inside the oikos; the basic unit of production, with the participation of both women and men, taking into account the sexual division of work and the gender spaces. As a productive space, the oikos allowed the subsistence of the family, guaranteed its reproduction and thus the transmission of productive spaces to successive generations, joining production and reproduction. In this context, productive women’s works are an essential element for the subsistence of the domestic unit and a source of wealth. Thus, it was a key factor in Greek economy.